2000
DOI: 10.4049/jimmunol.164.5.2602
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Macrophage Colony-Stimulating Factor in the Innate Immune Response toPneumocystis cariniiPneumonia in Mice

Abstract: Innate immunity plays an important role in pulmonary host defense against Pneumocystis carinii, an important pathogen in individuals with impaired cell-mediated immunity. We investigated the role of GM-CSF in host defense in a model of P. carinii pneumonia induced by intratracheal inoculation of CD4-depleted mice. Lung GM-CSF levels increased progressively during the infection and were significantly greater than those in uninfected controls 3, 4, and 5 wk after inoculation. When GM-CSF gene-targeted mice (GM ؊… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
114
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 52 publications
3
114
1
4
Order By: Relevance
“…Consistent with this notion, the intravenous administration of non-degradable pegylated GM-CSF resulted in high dendritic cell numbers that, paradoxically, increased the susceptibility of the mice to Listeria monocytogenes and M. tuberculosis despite elevated adaptive responses. 30 While previous studies demonstrated that GM-CSF levels in the lung influence the clearance rate of a number of pulmonary infections, [20][21][22][23] the present study reports that GM-CSF levels do not influence the clearance of the attenuated Mycobacterium bovis BCG or the establishment of the virulent M. tuberculosis H37Rv. Our results in GM-CSF −/− mice demonstrate that GM-CSF has a critical early role in preserving the integrity of alveolar epithelial cells in the presence of virulent M. tuberculosis infection.…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…Consistent with this notion, the intravenous administration of non-degradable pegylated GM-CSF resulted in high dendritic cell numbers that, paradoxically, increased the susceptibility of the mice to Listeria monocytogenes and M. tuberculosis despite elevated adaptive responses. 30 While previous studies demonstrated that GM-CSF levels in the lung influence the clearance rate of a number of pulmonary infections, [20][21][22][23] the present study reports that GM-CSF levels do not influence the clearance of the attenuated Mycobacterium bovis BCG or the establishment of the virulent M. tuberculosis H37Rv. Our results in GM-CSF −/− mice demonstrate that GM-CSF has a critical early role in preserving the integrity of alveolar epithelial cells in the presence of virulent M. tuberculosis infection.…”
Section: Introductionmentioning
confidence: 52%
“…Based on the above findings and previous results showing that lung GM-CSF significantly alters infection levels in the lungs, [20][21][22] we then tested the hypothesis that high-dose mycobacterial infection would be cleared differently from the lungs of WT, GMKO, and GMOE mice. On the contrary, Figure 2A demonstrates that both the early clearance and persistence of pulmonary BCG was similar in all mice.…”
Section: Similar Rates Of Mycobacterial Infection In Wt Gmko and Gmmentioning
confidence: 99%
See 3 more Smart Citations